2013
DOI: 10.1186/cc11937
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic consequences of borderline dysnatremia: pay attention to minimal serum sodium change

Abstract: IntroductionTo assess the prevalence of dysnatremia, including borderline changes in serum sodium concentration, and to estimate the impact of these dysnatremia on mortality after adjustment for confounders.MethodsObservational study on a prospective database fed by 13 intensive care units (ICUs). Unselected patients with ICU stay longer than 48 h were enrolled over a 14-year period were included in this study. Mild to severe hyponatremia were defined as serum sodium concentration < 135, < 130, and < 125 mmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 26 publications
10
86
1
13
Order By: Relevance
“…The definitions of mild, moderate and profound hyponatraemia in published research are variable, especially the threshold used to define profound hyponatraemia for which values have ranged from 110 to 125 mmol/l (64,65). Several studies report that when serum sodium concentrations drop below 125 mmol/l, symptoms become more common (61,66,67,68,69,70,71), and the correction to normonatraemia necessitates careful monitoring to avoid overly rapid correction (72).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The definitions of mild, moderate and profound hyponatraemia in published research are variable, especially the threshold used to define profound hyponatraemia for which values have ranged from 110 to 125 mmol/l (64,65). Several studies report that when serum sodium concentrations drop below 125 mmol/l, symptoms become more common (61,66,67,68,69,70,71), and the correction to normonatraemia necessitates careful monitoring to avoid overly rapid correction (72).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…La natrémie est habituellement finement régulée et ses valeurs physiologiques sont comprises entre 138 et 142 mmol/l [3]. Une natrémie inférieure ou égale à 135 mmol/l définit habituellement l'hyponatrémie (Tableau 1) [4] ; sa prévalence en réanimation varie de 17 à 28 % selon les études [5,6]. La majorité est faite d'hyponatrémies dites légères (natrémie entre 130 et 135 mmol/l), avec une prévalence de 15 à 20 % [5][6][7].…”
Section: Introductionunclassified
“…Une natrémie inférieure ou égale à 135 mmol/l définit habituellement l'hyponatrémie (Tableau 1) [4] ; sa prévalence en réanimation varie de 17 à 28 % selon les études [5,6]. La majorité est faite d'hyponatrémies dites légères (natrémie entre 130 et 135 mmol/l), avec une prévalence de 15 à 20 % [5][6][7]. Une natrémie supérieure ou égale à 155 mmol/l définit habituellement l'hypernatrémie (Tableau 1) [4].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…First, in our opinion, hyponatremia-defined as a plasma sodium level below 135 mmol/L-probably occurs much more frequently than indicated and is not exclusively related to cancer, especially in the elderly population, which exhibits comorbidities such as cardiovascular disorders and a multitude of concomitant medications. Darmon et al studied an unselected population of 11,125 patients hospitalized in intensive care and found that 3047 patients (27.4 %) had mild to severe hyponatremia (defined as a sodium concentration <130 mmol/L), and 2258 patients (20.3 %) had borderline hyponatremia (defined as a sodium concentration <135 mmol/L) at the time of ICU admission-that is, hyponatremia was diagnosed for 47.7 % of the studied population [2]. Second, uncertainty persists concerning the diagnosis of SIADH.…”
mentioning
confidence: 98%